Making comics - Barry, Lynda 1956- (Drawn & Quarterly, 2019)
"For more than five years the cartoonist Lynda Barry has been an associate professor in the University of Wisconsin-Madison art department and at the Wisconsin Institute for Discovery, teaching students from all majors, both graduate and undergraduate, how to make comics, how to be creative, how to not think. There is no academic lecture in this classroom. Doodling is enthusiastically encouraged. Making Comics is the follow-up to Barry's bestselling Syllabus and this time she shares all of her comics-making exercises. In a new hand drawn syllabus detailing her creative curriculum, Barry has students drawing themselves as monsters and superheroes, convincing students who think they can't draw that they can, and most important, encouraging them to understand that a daily journal can be anything so long as it is hand drawn."--
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Barry, Lynda -- 1956-; Comic books, strips, etc / Authorship; Creation (Literary, artistic, etc.) / Study and teaching; Art; Graphic Novels as Topic; Zeichnen; Comic